Posttraumatic Stress Disorder in the Primary Care Setting: Summary of Recommended Care. Issue 2 (March 2019) - Spottswood, Margaret; Fortney, John; Chen, Jessica A.; Davydow, Dimitry; Huang, Hsiang
Abstract: Posttraumatic stress disorder (PTSD) occurs following acute threatening events in approximately 12.5% of the primary care population. Objective: The aim of this article is to advance evidence-based clinical practice and collaborative care approaches to PTSD by summarizing targeted-care guidelines. Method: This narrative literature review addresses important aspects of PTSD and management options, in conjunction with expert opinion when indicated. Guidelines were included if they targeted treatment of PTSD in the primary care setting or if the treatments described could be provided in the primary care setting. Results: The implications regarding PTSD, comorbidities, differential diagnosis, screening tools, and treatment are presented. Conclusion: Primary care providers can diagnose and offer initial management of PTSD. Future research should delineate therapies helpful for complex PTSD, including group therapies, those increasing self-compassion, and other optimally effective collaborative care interventions.